Introduction to quantum mechanics - Griffiths, David J (David Jeffery), 1942- (Noida : Pearson, 2017)
"This text first teaches students how to do quantum mechanics, and then provides them with more insightful discussion of what it means. Fundamental principles are covered, quantum theory presented, and special techniques developed for attacking realistic problems. Two-part coverage organizes topics under basic theory, and assembles an arsenal of approximation schemes with illustrative applications." --
The wave function -- Time-Independent Schrèodinger equation -- Formalism -- Quantum mechanics in three dimensions -- Identical particles -- Time-Independent perturbation theory -- The variational principle -- The WKB approximation -- Time-Dependent perturbation theory -- The adiabatic approximation -- Scattering.
Equations, and formulas on lining papers.
"This book was previously published by Pearson Education, Inc. 2004. Reissued by Cambridge University Press 2017"--T.p. verso.
Includes index.
Keywords: Quantum theory; Quantum theory -- Study and teaching